ANALISIS IMPLEMENTASI KOMPETENSI PENGUJI KENDARAAN DI UNIT PELAKSANA UJI BERKALA KENDARAAN BERMOTOR DINAS PERHUBUNGAN KABUPATEN PROBOLINGGO - jurnalmap map; Sugiono ÔÇÄ; Woro Utari (MAP (Jurnal Manajemen dan Administrasi Publik), 2021)
The purpose of this study to examine the implementation of service quality testing of motor vehicles in UPUBKB Probolinggo District Department of Transportation. This study uses descriptive analysis with qualitative approach, data collection techniques using the technique of the interview, conducted to the Chief UPUBKB, Testers Technical and business vehicles, observation, documentation, primary data and sekuder that was obtained is processed through qualitative procedures include data reduction, presentation Data and data verification or conclusion. The results showed that the Quality of Service Testing Vehicle in UPUB not provide optimum service. It is seen from the quantity of human resources limited, competency testing, facilities and infrastructures are inadequate and the limited understanding of the community about vehicle testing service procedures. Keywords: competence, service, motor vehicle testing